COVID-19 and diarrhea: putative mechanisms and management. (January 2023) - Juthi, Rifat Tasnim; Sazed, Saiful Arefeen; Sarmin, Monira; Haque, Rashidul; Alam, Mohammad Shafiul
Highlights: The mechanism of diarrhea in COVID-19 is mainly associated with angiotensin-converting enzyme 2. Altered gut microbiota and side effects of medications can lead to diarrhea. Diversified medications are used to manage the complications. Abstract: Background: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the causative agent of the coronavirus disease 2019 (COVID-19), has recently posed a threat to global health by spreading at a high rate and taking millions of lives worldwide. Along with the respiratory symptoms, there are gastrointestinal manifestations and one of the most common gastrointestinal symptoms is diarrhea which is seen in a significant percentage of COVID-19 patients. Literature review: Several studies have shown the plausible correlation between overexpressed angiotensin converting enzyme 2 (ACE2) in enterocytes and SARS-CoV-2, as ACE2 is the only known receptor for the virus entry. Along with the dysregulated ACE2, there are other contributing factors such as gut microbiome dysbiosis, adverse effects of antiviral and antibiotics for treating infections and inflammatory response to SARS-CoV-2 which bring about increased permeability of gut cells and subsequent occurrence of diarrhea. Few studies found that the SARS-CoV-2 is capable of damaging liver cells too. No single effective treatment option is available. Limitations: Confirmed pathophysiology is still unavailable. Studies regarding global population are also insufficient. Conclusion: In this review, based on the previous works and literature, we summarized the putative molecular pathophysiology of COVID-19 associated diarrhea, concomitant complications and the standard practices of management of diarrhea and hepatic manifestations in international setups.